PERKAWINAN TRADISIONAL MASYARAKAT KEI DALAM PERSPEKTIF TEORI KEKERABATAN CLAUDE LÉVI-STRAUSS - Refo, Ignasius SS. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2013)
According to Lévi-Strauss, there are two different structural models of marriage exchange. First, the women of Ego's group areoffered to another group explicitly defined by social institutions. This is the elementary structure of kinship. Secondly, the group ofpossible spouses for the women in ego's group is "indetermined and always open", with exclusion, however, of certain kin-people.Lévi-Strauss calls these latter complex structures of kinship. The model of Levi-Strauss attempts to offer a single explanation forcross-cousin marriage, sister-exchange, dual organisation and rules of exogamy. Marriage rules over the times create social structures, as marriages are primarily forged between groups and not just between the two individuals involved